ANALYSIS OF IMAM AL-MAWARDI'S VIEWS ON THE PRACTICE OF RISYWAH IN THE DPR/DPRD ELECTIONS AND ITS RELEVANCE TO THE ELECTION SYSTEM IN INDONESIA - Aulia Sabrina Hasibuan; Zulkifli Nas (Program Pascasarjana UIN Sumatera Utara, 2026)
Money politics in the election of members of the House of Representatives (DPR) and Regional House of Representatives (DPRD) remains a serious challenge to electoral integrity in Indonesia because it weakens voters’ political autonomy, distorts representation, and undermines the principle of fair elections. In Islamic legal thought, this practice is closely related to risywah, namely the use of material incentives to influence public decisions or obtain political office. This study aims to analyze Imam al-Mawardi’s concept of risywah, examine its relation to Indonesian electoral law, and formulate its relevance for strengthening the ethical foundation of Indonesia’s electoral system. This research employs a normative juridical method using conceptual, statutory, and historical approaches through library research on classical Islamic legal texts, electoral legislation, and relevant scholarly literature. The findings show that al-Mawardi’s thought offers a normative-ethical framework for understanding money politics as a defect in political legitimacy. Risywah not only violates legal norms but also eliminates ‘adālah as a fundamental requirement of leadership, damages public trust, and contradicts the objectives of governance based on amānah and maṣlaḥah. The novelty of this study lies in positioning al-Mawardi’s political thought as an ethical corrective to the formalistic enforcement of electoral law in Indonesia. Therefore, strengthening electoral integrity requires not only legal sanctions but also the internalization of Islamic political ethics, public education, and consistent supervision against transactional politics